Relationship between patent ductus arteriosus and platelet indices in newborn: a systematic review and meta-analysis - An, Yanbing; Arigong, Gaowa; Zhao, Wuyun; Su, Rina; Wang, Xiaoyun (Frontiers in Pediatrics, 2025)
BackgroundThe role of platelet indices in the early hours of life and their potential association with patent ductus arteriosus (PDA) have been subjects of investigation in recent studies. This study aimed to investigate the relationship between PAD and platelet indices in newborn.MethodsA systematic review and meta-analysis and were preformed based on Chinese databases CNKI and Wanfang database, as well as the international databases PubMed, Web of Science, Cochrane Library, and Embase from their inception to January 31, 2024.ResultsThis study included 32 literatures, with 20 of English and 12 of Chinese ones. The meta regression analysis showed that neonates with PDA tend to exhibit lower platelet count (PLT) and plateletcrit (PCT), as well as higher platelet large cell ratio (P-LCR) (all P < 0.05), while platelet mass, platelet distribution width (PDW), and mean platelet volume (MPV) remain comparable (all P > 0.05).ConclusionPDA neonates might have decreased PLT and PCT, while increased P-LCR. These dynamic shifts in platelet indices provide fresh insights into the pathophysiology of PDA and have potential to serve as important indicators for early identification, disease assessment, and personalized treatment decisions in clinical practice.